Hubungan Religiositas dengan Moralitas: Studi pada Mahasiswa Program Studi Pendidikan Agama Kristen, IAKN Kupang - Marthen Nawa Bangngu; Ezra Tari; Johana Manubey (Sekolah Tinggi Teologi Baptis, Jakarta, 2023)
Morality in the campus environment tells about the lives of students which talks about the actions and behavior of students from Christian education backgrounds—problems about my actions and behavior that can still do things that violate morality. Students can apply a moral life on campus and in the community. First, this study aims to determine the level of religiosity among students of the Kupang State Christian Institute for the 2019 Christian Religious Education study program. Second, the level of morality in the students of the Kupang State Christian Institute for the Study of Christian Religious Education, class 2019. The third is to prove the relationship between religiosity and morality in students. Kupang State Christian Institute, Class of 2019. This study uses a quantitative approach. Based on the results of the research analysis proves that the level of student religiosity is very high. The percentage level of student morality is high. The correlation test results show a significant relationship between religiosity and the morality of students at the Kupang State Christian Institute, Christian Religious Education Study Program. AbstrakMoralitas dilingkungan kampus yang bercerita tentang kehidupan para mahasiswa yang didalamnya berbicara tentang perbuatan dan tingkah laku/ahklak para mahasiswa yang berlatar belakang mahasiswa pendidikan Kristen. Masalah tentang perbuatan dan tingkalaku yang masih kedapat melakukan perbuatan yang melanggar moralitas. Mahasiswa mampu menerapkan kehidupan yang bermoral di lingkungan kampus maupun di masyarakat. Penelitian ini bertujuan untuk mengetahui hubungan antara religiositas dengan moralitas, berdasarkan studi kasus pada mahasiswa Institut Agama Kristen Negeri Kupang, Program Studi Pendidikan Agama Kristen angkatan 2019. Penelitian ini menggunakan pendekatan kuantitatif. Berdasarkan hasil analisis penelitian membuktikan tingkat religiositas mahasiswa sangat tinggi. Persentase tingkat moralitas mahasiswa tinggi. Dari hasil uji korelasi terdapat hubungan yang signifikan antara religiositas dengan moralitas mahasiswa Institut Agama Kristen Negeri Kupang, Program Studi Pendidikan Agama Kristen.